Proceedings of the Fourteenth ACM International Symposium on Mobile Ad Hoc Networking and Computing 2013
DOI: 10.1145/2491288.2491308
|View full text |Cite
|
Sign up to set email alerts
|

Realtime streaming with guaranteed QoS over wireless D2D networks

Abstract: We consider a group of co-located wireless peer devices that desire to synchronously receive a live content stream. The devices are each equipped with an expensive unicast basestation-to-device (B2D) interface, as well as a broadcast device-to-device (D2D) interface over a shared medium. The stream is divided into blocks, which must be played out soon after their initial creation. If a block is not received within a specific time after its creation, it is rendered useless and dropped. The blocks in turn are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…The simulation result is shown in Figure 10, where x is the UE's subscript and y is the UE's reward. It can be found that the rewards of UEs (6)(7)(8)(9)(10), that are incapable of receiving data from the cellular network, increase with both the P2P transmission rate and the number of peers that provide relay service.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The simulation result is shown in Figure 10, where x is the UE's subscript and y is the UE's reward. It can be found that the rewards of UEs (6)(7)(8)(9)(10), that are incapable of receiving data from the cellular network, increase with both the P2P transmission rate and the number of peers that provide relay service.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…8,10,11,14 As discussed in section ''Video model,'' one video content consists of a sequence of a group of pictures/frames (GoPs). Accordingly, one common way is to perform RLC across all frames within one GoP, and then the resulting coded chunks are delivered to all users via the wireless networks.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [7], [8], the dissemination process of video content is divide into two stages: download over cellular B2D links and dissemination over local D2D links. They transform the optimization problem into choosing a subset of mobile devices serving as gateways between cellular local D2D networks, and present dissemination schemes that provide guidelines for video content transmission among individual users.…”
Section: Related Workmentioning
confidence: 99%